Disruption of the creb3l1 gene causes defects in caudal fin regeneration and patterning in zebrafish Danio rerio - VanWinkle, Peyton E. (2024)
BackgroundThe gene cAMP-Responsive Element Binding protein 3-like-1 (CREB3L1) has been implicated in bone development in mice, with CREB3L1 knock-out mice exhibiting fragile bones, and in humans, with CREB3L1 mutations linked to osteogenesis imperfecta. However, the mechanism through which Creb3l1 regulates bone development is not fully understood.ResultsTo probe the role of Creb3l1 in organismal physiology, we used CRISPR-Cas9 genome editing to generate a Danio rerio (zebrafish) model of Creb3l1 deficiency. In contrast to mammalian phenotypes, the Creb3l1 deficient fish do not display abnormalities in osteogenesis, except for a decrease in the bifurcation pattern of caudal fin. Both, skeletal morphology and overall bone density appear normal in the mutant fish. However, the regeneration of caudal fin postamputation is significantly affected, with decreased overall regenerate and mineralized bone area. Moreover, the mutant fish exhibit a severe patterning defect during regeneration, with a significant decrease in bifurcation complexity of the fin rays and distalization of the bifurcation sites. Analysis of genes implicated in bone development showed aberrant patterning of shha and ptch2 in Creb3l1 deficient fish, linking Creb3l1 with Sonic Hedgehog signaling during fin regeneration.ConclusionsOur results uncover a novel role for Creb3l1 in regulating tissue growth and patterning during regeneration.